1991
DOI: 10.1111/j.1439-0396.1991.tb00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Überhöhte Energie‐ oder Proteinversorgung von Milchkühen und die Ausscheidung verschiedener B‐Vitamine (Thiamin, Vitamin B6, Pantothensäure) mit der Milch

Abstract: Zusammenfassung Im Rahmen von zwei Stoffwechselversuchen von 16‐ bzw. neunwöchiger Dauer mit vier eineiigen Zwillingskuhpaaren bzw. 6 × 3 phänotypisch ähnlichen Kühen sollten die Auswirkungen eines Energieüberschusses von 20 MJ NEL/Tier und Tag (Versuch E) bzw. einer 25%igen Proteinüberversorgung (Versuch P) auf die Gehalte und Ausscheidungsmengen an Thiamin, Vitamin B6 und Pantothensäure in der Milch untersucht werden. Die Analysen erfolgten mikrobiologisch. Weder die Energie‐ noch die Proteinzulagen hatten s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…According to a review by Kirchgessner et al (1965) and two more recent studies by the same group (Kirchgessner et al, 1991a,b) milk PA concentrations range from 1.7 to 5.5 mg/l, which is similar to the PA values of the present study (4.5–6.6 mg/l). One previous study (Marsh et al, 1947) tested the influence of a B‐vitamin mix, consisted of PA, thiamine, riboflavin and nicotinic acid, on milk PA concentrations in dairy cows and goats.…”
Section: Discussionsupporting
confidence: 89%
“…According to a review by Kirchgessner et al (1965) and two more recent studies by the same group (Kirchgessner et al, 1991a,b) milk PA concentrations range from 1.7 to 5.5 mg/l, which is similar to the PA values of the present study (4.5–6.6 mg/l). One previous study (Marsh et al, 1947) tested the influence of a B‐vitamin mix, consisted of PA, thiamine, riboflavin and nicotinic acid, on milk PA concentrations in dairy cows and goats.…”
Section: Discussionsupporting
confidence: 89%
“…The average PA content in the milk was about 3 mg/l. Since then, only two further studies on milk PA concentrations were published (Kirchgessner et al., 1991a; b) (Table 5). In a compilation by Souci et al.…”
Section: Pantothenic Acid Concentrations In Blood Milk and Urinementioning
confidence: 99%
“…Kirchgessner et al. (1991a,b) reported that neither a prolonged release of bovine growth hormone nor an excess of energy or protein had an influence on PA concentrations in milk.…”
Section: Pantothenic Acid Concentrations In Blood Milk and Urinementioning
confidence: 99%